Dysregulation of circulating T follicular helper cell subsets and their potential role in the pathogenesis of syphilis - Shen, Fuping; Shen, Yuhuan; Xu, Yuni; Zhao, Jiwei; Zhao, Zhao; Liu, Jinlin; Ge, Yumei (Frontiers in Immunology, 2023)
The present study aimed to examine changes in cellular homeostasis in T follicular helper (Tfh) cells in secondary syphilis patients and latent patients. Thirty healthy controls (HCs), 24 secondary syphilis patients, and 41 latent syphilis patients were enrolled. The percentages of total Tfh, ICOS + Tfh, PD-1 + Tfh, resting Tfh, effector Tfh, naï ve Tfh, effector memory Tfh, central memory Tfh, Tfh1, Tfh2, and Tfh17 cells in the peripheral blood were all determined by flow cytometry. We found that the percentage of total Tfh cells was significantly higher in secondary syphilis patients compared to HCs across various subsets, including ICOS + Tfh, PD-1 + Tfh, resting Tfh, effector Tfh, naï ve Tfh, effector memory Tfh, central memory Tfh, Tfh1, Tfh2, and Tfh17 cells. However, only the percentages of ICOS + Tfh and effector memory Tfh cells showed significant increases in secondary syphilis patients and decreases in latent syphilis patients. Furthermore, the PD-1 + Tfh cells, central memory Tfh cells, and Tfh2 cells showed significant increases in latent syphilis patients, whereas naï ve Tfh cells and Tfh1 cells exhibited significant decreases in secondary syphilis patients when compared to the HCs. However, no significant change was found in resting Tfh and effector Tfh cell number in HCs and secondary syphilis patients or latent syphilis patients. Thus, dysregulated ICOS + Tfh or effector memory Tfh cells may play an important role in immune evasion in latent syphilis patients.